Analysis of Critical Management Factors for Managing Safety and Health of High Rise Building Construction Projects - Murali, Kishen; Deraman, Rafikullah (Recent Trends in Civil Engineering and Built Environment, 2021)
Safety and health issues had always been a major challenge and concern in the construction industry. This study aims to identify the critical management factors on safety and health management practices in high-rise building projects, considering that the current research is a lack understanding of these factors within this particular context. The questionnaire survey was carried out, targeting respondents from high rise building projects at Johor and Melaka. The data are analyzed using frequency and percentage distributions to score to measure respondent demographics. Meanwhile, the agreement on the critical management factors was analyzed using mean score and the Relative Importance Index (RII). Moreover the RII was also used to determine the significance of critical management factors and rank the factors. Based on the findings, occupational safety and health committee (RII = 0.821; mean 4.10) are the most influential critical factor among 13 factors for managing safety and health of high-rise building construction projects. The finding of this study helps the practitioner to more careful attention to critical management factors that will be impacting the success of safety and health management for construction high-rise building projects